Promotion of Brand in Rural Market - Bagla, Ashish; Gupta, Vivek (Journal of Commerce and Trade, 2008)
Promotion of brands in rural markets requires the special measures. Due to the social and backward condition the personal selling efforts have a challenging role to play in this regard. The Indian established Industries have the advantages, which MNC don’t enjoy in this regard. The strong Indian brands have strong brand equity, consumer demand-pull and efficient and dedicated dealer network which have been created over a period of time. The rural market has a grip of strong country shops, which affect the sale of various products in rural market. The companies are trying to trigger growth in rural areas. They are identifying the fact that rural people are now in the better position with disposable income. The low rate finance availability has also increased the affordability of purchasing the costly products by the rural people. Marketer should understand the price sensitivity of a consumer in a rural area. This paper is therefore an attempt to promote the brand image in the rural market.